THE RELATIONSHIP BETWEEN SELF-CONFIDENCE, SELF-REMEMBRANCE AND SINCERITY AMONG STAFF TOWARDS INFORMATION SYSTEMS OUTSOURCING SUCCESS - Mohd Amir MAT SAMSUDIN; Mohamad Hisyam SELAMAT; Ram Al-Jaffri SAAD; Muhammad Syahir ABDUL WAHAB (Studia Universitatis Babeş-Bolyai Negotia, 2017)
The study examines the relationship between the humanistic elements of self-confidence, self-remembrance and sincerity among staff towards the success of information systems (IS) outsourcing. A total of 500 questionnaires were distributed by mail to the manager of information systems outsourcing companies registered with Malaysia's Multimedia Super Corridor and 168 were returned. The hypotheses of this study were analyzed using multiple regression methods. The findings show that the element of self-confidence and sincerity of the staff have a positive and significant relationship towards the success of information systems outsourcing. The theoretical and practical implications and suggestions for future research are discussed.